ABILITIES OF THERAPY FOR DYSHORMONAL MAMMARY GLAND PATHOLOGY IN FEMALES WITH GYNECOLOGICAL DISEASES - T. V. Ovsyannikova (IRBIS LLC, 2016)
Benign alterations of mammary glands are the most common diseases in women. The fibrocystic breast disease (FCBD) is the most common benign disease of mammary glands at that. One of the etiologic factors of breast disease occurrence are believed to be conditions which are due to reduced progesterone level at the backdrop of excess estrogen level, which brings about proliferation of mammary gland tissue and disorders of its receptor apparatus. The most characteristic clinical manifestations of FCBD are breast tenderness (mastodynia) with possible irradiation, sensation of breast size enlargement, breast engorgement and swelling. Often, the mastopathy symptoms are combined with pre menstrual syndrome. Methods of treatment of mammary gland diseases are selected individually, taking into account factors affecting the pathological condition. Currently, the plant derived medications are widely used for treatment, such as Mamoclam andMastodion, as well as a transdermal preparation Progestogel. In the FCBD females on a long term COC treatment an improved mammary gland condition is observed. This treatment effect is due to normalization of hormonal parameters and menstrual period, reduction of rate of functional ovarian cysts' formation and frequency of inflammatory genital diseases.